ANALISIS SEMANTIK TENTANG MAKNA LU’LU DALAM AL-QUR’AN: KAJIAN TERHADAP PEMAHAMAN TOSHIHIKO IZUTSU - Rizky, Fathullah (ojs.unsiq.ac.id, 2024)
The Quran, as the holy scripture, continues to provide freshness through various interpretations without altering its essence and the value of its messages. The study of Quranic exegesis and various interpretative models has evolved over time, creating a vast wealth of knowledge. Since the time of Prophet Muhammad, scholars have made numerous efforts to uncover the meanings and content embedded in the Quran. They have employed diverse methods to delve into the core concepts presented by the Quran. Toshihiko Izutsu, with the ambition to address all issues related to keywords in the Quran, developed an ambitious method utilizing semantic analysis to facilitate researchers and scholars in interpreting Quranic verses by identifying key terms. This article delves into the diverse meanings of the terms